Oxidative stress as a hidden cost of attractiveness in postmenopausal women - Marcinkowska, Urszula M; Ziomkiewicz, Anna; Kleisner, Karel; Galbarczyk, Andrzej; Klimek, Magdalena; Sancilio, Amelia; Jasienska, Grazyna; Bribiescas, Richard G (Scientific reports, 2020)
Perceived facial attractiveness, a putative marker of high biological fitness, is costly to maintain throughout a lifetime and may cause higher oxidative stress (OS). We investigated the association between the facial features of 97 postmenopausal women and their levels of OS biomarkers 8-hydroxy-2'-deoxyguanosine (8-OHdG), superoxide dismutase (Cu-Zn SOD), and thiobarbituric acid reactive substances (TBARS). In study 1, 966 judges rated the composites (facial averages) of women with higher OS as more attractive, healthier, younger, and less symmetric. In study 2, Geometric Morphometric analysis did not reveal significant differences in facial morphology depending on OS levels. In study 3, measured facial averageness and symmetry were weakly negatively related to 8-OHdG levels. Maintaining higher perceived facial attractiveness may be costly due to increased oxidative damage in the postmenopausal period. These costs may remain hidden during the reproductive period of life due to the protective mechanisms of oxidative shielding and revealed only after menopause when shielding has ceased.
Keywords: senioři; obličej; 8-hydroxy-2'-deoxyguanosin; postmenopauza; senioři nad 80 let; Middle Aged; Oxidative Stress; regresní analýza; Aged, 80 and over; Postmenopause; Humans; 8-Hydroxy-2'-Deoxyguanosine; Face; biologické markery; lidé středního věku; Regression Analysis; oxidační stres; Biomarkers; Aged; lidé